The Long Journey of Pontine Nuclei Neurons: From Rhombic Lip to Cortico-Ponto-Cerebellar Circuitry - Kratochwil, Claudius F.; Maheshwari, Upasana; Rijli, Filippo M. (Frontiers in Neural Circuits, 2017)
The pontine nuclei (PN) are the largest of the precerebellar nuclei, neuronal assemblies in the hindbrain providing principal input to the cerebellum. The PN are predominantly innervated by the cerebral cortex and project as mossy fibers to the cerebellar hemispheres. Here, we comprehensively review the development of the PN from specification to migration, nucleogenesis, and circuit formation. PN neurons originate at the posterior rhombic lip and migrate tangentially crossing several rhombomere derived territories to reach their final position in ventral part of the pons. The developing PN provide a classical example of tangential neuronal migration and a study system for understanding its molecular underpinnings. We anticipate that understanding the mechanisms of PN migration and assembly will also permit a deeper understanding of the molecular and cellular basis of cortico-cerebellar circuit formation and function.